Outcomes after hypofractionated stereotactic radiotherapy for colorectal cancer oligometastases. Issue 4 (4th January 2019) - Yu, Jing; Li, Ning; Tang, Yu; Wang, Xin; Tang, Yuan; Wang, Shu‐Lian; Song, Yong‐Wen; Liu, Yue‐Ping; Li, Ye‐Xiong; Jin, Jing
Abstract : Background and Objectives: To assess the efficacy and the effect of biologic effective dose (BED) on outcomes treated by hypofractionated stereotactic radiotherapy for colorectal cancer (CRC) oligometastases. Methods: Patients with CRC oligometastases treated at our hospital between 2009 and 2016 were included. The relationship between BED and risk of local recurrence was assessed. Recursive partitioning analysis (RPA) was used to evaluate the effect of BED on outcomes. Results: A total of 48 patients were included in this study. Median follow‐up time of surviving patient was 15 months (range, 3‐82 months). The 1‐year local control rate was 85%. The risk of local recurrence decreased sharply when BED was >90 Gy10 . RPA showed BED of 100 Gy10 was the appropriate dose for recurrence risk stratification. BED ≥ 100 Gy10 was significantly better than BED < 100 Gy10 for achieving 1‐year local control (94.4% vs 63.2%; P = 0.022) and 1‐year OS (100% vs 73.4%; P = 0.028). One patient who received long‐term antiangiogenic treatment died of massive intestinal hemorrhage; no other grade 3 or above early or late events were observed. Conclusions: Hypofractionated stereotactic radiotherapy provides favorable outcomes with acceptable toxicities in CRC oligometastases. BED ≥ 100 Gy is associated with better outcomes.